Biomass and Nutrient Accumulation by Dual-Purpose Hemp and Concurrent Soil Profile Water Depletion at Two Locations in Kansas in 2020 - Kraig Roozeboom; Jason Griffin; Lucas Haag; Gerard Kluitenberg; Dorivar Ruiz Diaz; Michael Shelton; Tami Myers; Clint Wilson; Jared Petz; Matthew Nielsen; Andrew Euler (Kansas Agricultural Experiment Station Research Reports, 2021)
Some crop producers are considering hemp as an alternative to the typical crops grown in the region. Hemp is viewed as a crop to potentially access new markets. Two of those potential markets are hemp grain and fiber. Little information is available for this region about production management for hemp intended for those markets. Experiments were planted in 2020 at Manhattan, Haysville, and Colby, KS, to characterize plant growth, nutrient uptake, and soil water depletion. Results illustrated typical biomass and nutrient uptake patterns. Half of the total biomass was accumulated by 2,200 growing degree days (GDD), but accumulation continued until harvest at 4,200 GDD. Nitrogen (N) and potassium (K) accumulated more rapidly than dry biomass, with half of their total uptake at 2,000 and 1,700 GDD, respectively. Phosphorus (P) accumulation was similar to biomass accumulation. Hemp accumulated more than 7,000 pounds of dry biomass/acre that contained roughly 170 lb nitrogen, 13 lb of phosphorus, and113 lb potassium/acre. Soil profile water was depleted by 4.3 to 6.9 inches during hemp growth with 11 to 18 inches of precipitation falling during the season. Some portion of the precipitation ran off before infiltrating the profile, and some may have drained through the rooting zone. These values represent data collected at only two sites and are only preliminary estimates. More information is needed from a wider range of growing conditions to better quantify biomass, nutrient accumulation, and soil water depletion by hemp.
Keywords: biomass; dual-purpose hemp; soil water depletion; hemp water use; biomass hemp; Kansas hemp production; hemp nutrient accumulation